Prototipo de camineras con plásticos reciclados para reemplazo de madera en el muelle del Parque Histórico, Samborondon - Ledesma Anchundia, Nelvyn Alexander (2025)
This study evaluates the technical, economic, and environmental feasibility of replacing the Chanul wood pieces used in the walkways of the Samborondón Historical Park pier with a prototype of staves made of recycled plastics and a metal core. The research includes a comparison of the physical and mechanical properties of both materials through bending and abrasion tests, as well as an analysis of their dimensions, weight, and structural compatibility. The results indicate that, although Chanul wood has greater mechanical resistance, plastic lumber meets the established load requirements, offering advantages such as absence of manufacturing waste, lower maintenance costs, and a projected useful life of 20 years, compared to the four years of recurrent replacement for Chanul. The budget analysis shows that, although the initial installation cost of plastic lumber is higher, its use represents significant long term savings, in addition to contributing to sustainability through the reuse of plastic waste. It is concluded that the progressive implementation of the plastic-wood prototype is a viable and sustainable alternative to improve the durability and reduce the environmental impact of the Historic Park's pedestrian infrastructure.